Business ethics 3rd edition - Khalid Ali, Khalidah (SJ Learning, 2026)
Business Ethics 3e, attractively presented in vibrant colours to signify diversity, is a clear and thoughtful introduction to ethical decision making from individual, organisational and societal perspectives. This comprehensive textbook specially caters for undergraduate students pursuing business, accounting and entrepreneurship courses at higher learning institutions. Building from its second edition (2018), contemporary business issues have been incorporated and deliberated from economic, legal and moral/ethical perspectives. Encapsulating 13 chapters, this textbook begins with the fundamental concepts, theories and principles of business ethics, followed by important topics such as ethical leadership and corporate culture, corporate governance, corporate social responsibility (CSR), business ethics and information technology (IT), ethics and the environment as well as ethics in the global environment. Additionally, this edition directly engages with real-world cases and dilemmas facing business organisations nowadays, mostly drawn from the Malaysian and Asian experiences. An added chapter on artificial intelligence, ethics and society, has been crafted and included to bridge innovation and accountability. 32 relatable new cases, (well spread in each of the 13 chapters’ content as well as end-of chapter case study sections) have been included for practical discussions.